(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In modern professional sports, the relationship between a coach and a sports club (or federation) possesses a complex legal nature and is governed by both labour law and specific norms of sports law. In practice, the unilateral termination of a contract by a club (for example, due to unsatisfactory sporting results) is a common occurrence and has been widely examined. However, the unilateral termination of a contract by a coach has been comparatively under-researched, despite constituting a pressing legal issue that may lead to highly contentious consequences in practice. The unilateral termination of a sports contract by a coach typically occurs for two main reasons: first, within the framework of “just cause” - for instance, in cases of systematic non-payment of salary by the club or unlawful interference with the coach’s professional activities; and second, “without just cause” - such as when the coach receives a more favorable financial offer. Although national labour laws generally guarantee an employee’s right to terminate an employment contract at their own discretion, in sports law and in the jurisprudence of the Court of Arbitration for Sport, the principle of contractual stability is considered paramount. This creates a legal conflict between national labour codes and international sports law. The purpose of this thesis is to analyse the legal grounds for the unilateral termination of a sports contract by a coach, the criteria for recognizing such termination as lawful (with just cause), and the legal and financial consequences arising from such actions for the parties involved, including obligations to pay compensation.